Optogenetic fMRI reveals therapeutic circuits of subthalamic nucleus deep brain stimulation - Yuhui Li; Sung-Ho Lee; Chunxiu Yu; Li-Ming Hsu; Tzu-Wen W. Wang; Khoa Do; Hyeon-Joong Kim; Yen-Yu Ian Shih; Warren M. Grill (Brain Stimulation, 2024)
While deep brain stimulation (DBS) is widely employed for managing motor symptoms in Parkinson's disease (PD), its exact circuit mechanisms remain controversial. To identify the neural targets affected by therapeutic DBS in PD, we analyzed DBS-evoked whole brain activity in female hemi-parkinsonian rats using functional magnetic resonance imaging (fMRI). We delivered subthalamic nucleus (STN) DBS at various stimulation pulse repetition rates using optogenetics, allowing unbiased examination of cell-type specific STN feedforward neural activity. Unilateral optogenetic STN DBS elicited pulse repetition rate-dependent alterations of blood-oxygenation-level-dependent (BOLD) signals in SNr (substantia nigra pars reticulata), GP (globus pallidus), and CPu (caudate putamen). Notably, this modulation effectively ameliorated pathological circling behavior in animals expressing the kinetically faster Chronos opsin, but not in animals expressing ChR2. Furthermore, mediation analysis revealed that the pulse repetition rate-dependent behavioral rescue was significantly mediated by optogenetic DBS induced activity changes in GP and CPu, but not in SNr. This suggests that the activation of GP and CPu are critically involved in the therapeutic mechanisms of STN DBS.